2008
DOI: 10.1128/jcm.01455-08
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Methods for Rapid Detection of Resistance to Isoniazid and Rifampin in Mycobacterium tuberculosis Isolates Collected in the Caribbean

Abstract: The rapid identification of drug-resistant strains of Mycobacterium tuberculosis is crucial for the timely initiation of appropriate antituberculosis therapy. The performance of the Genotype MTBDRplus assay was compared with that of the Bactec 460 TB system, a "gold standard" culture-based method. The Genotype MTBDRplus assay was quicker and more cost-effective for the detection of rifampin resistance, but it was not as good for the detection of isoniazid-resistant strains in our setting.The major serious chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
12
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 9 publications
5
12
1
2
Order By: Relevance
“…The frequency of the major mutation S531L (63.2%) is consistent with those found in other studies (50% and 86%) (1,4,6,10,15,21). Our results were consistent despite reports that the D516V mutation was commonly found (38%) in Hungarian strains (5), while it was not common in our MDR isolates (2%) (data not shown).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The frequency of the major mutation S531L (63.2%) is consistent with those found in other studies (50% and 86%) (1,4,6,10,15,21). Our results were consistent despite reports that the D516V mutation was commonly found (38%) in Hungarian strains (5), while it was not common in our MDR isolates (2%) (data not shown).…”
Section: Discussionsupporting
confidence: 78%
“…This test is useful due to its accuracy and specificity, as well as its short turnaround time and ease of use. Previous studies have demonstrated that the GenoType MTBDRplus test had outstanding performance: 91.7% to 100% accuracy in detecting RIF resistance, 34.6% to 94.6% accuracy in detecting INH resistance, and 92% to 100% accuracy in detecting MDR (1,4,6,10,15,21). In comparison, the GenoType MTBDRplus test identified 95.4% of RIF-resistant isolates, 81.8% of INH-resistant isolates, and 78.5% of MDR isolates in our study.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…[32][33][34][35][36][37][38][39][40][41][42] Conceptually similar to the INNO-Lipa Rif.tb assay, the MTBDRplus assay has been reported to have a diagnostic sensitivity of approximately 94% for detecting M tuberculosis DNA in smear-positive respiratory specimens. 33 It is of interest that most clinical evaluations of this device have focused on its use for susceptibility testing, not detection of M tuberculosis, so the performance characteristics for the latter use are less well defined.…”
Section: Line Probe Assaysmentioning
confidence: 99%
“…정도로 보고된 것과 유사하다 [11, 16-19, 22, 23, 25]. 하지만 캐리비 안 지역에서 실시한 연구에서는 34.6%로 훨씬 낮아서 지역에 따라 상당한 차이를 보인다 [14]. …”
unclassified